Shifting Conceptions of Social (IN) Justice in Nepal - Pravat, Poshendra Satyal (New Angle: Nepal Journal of Social Science and Public Policy, 2011)
The purpose of this paper is to analyse and situate the changing discourses of social (in)justice in the context of political transition and restructuring process that Nepal has gone through since 2006. This paper discusses the origin and development of the discourse and analyses how its meaning has changed over time. As the paper argues, the earlier discourses of social justice in Nepal can be linked to the Hindu and Buddhist notion of dharma and various other ethnic cultural traditions. After Janandolan-I in 1990, the policy and practice of social justice began to be equated with the principle of equality, which was based on the assumptions of sameness. After Janandolan-II in 2006, the public conception of social justice has shifted towards a more vocal emphasis on social equity, inclusiveness, proportionate representation and participatory decision-making. The article provides empirical manifestations of social injustices in Nepal, linking them with various discourses and traditions of justice in the early and modern historical, socio-cultural and political contexts. It is hoped that a thorough understanding of historical shifting of public conceptions of social (in)justice in Nepal will be useful in guiding the country’s future public policies towards inclusive restructuring and equitable development.